Postprocedural Interpretation of Endoscopic Retrograde Cholangiopancreatography by Radiology - Nitin Khanna; Gary May; Sydney Bass; Marty Cole; Joseph Romagnuolo (Canadian Journal of Gastroenterology)
BACKGROUND: With the increase in the use of endoscopic retrograde cholangiopancreatography (ERCP) (necessitating real-time interpretation), it is unknown whether post-ERCP radiologist reporting is still necessary or helpful.